2016
DOI: 10.11607/ijp.4287
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetry Impression Technique: A Case History Report

Abstract: Purpose: The aim of this report is to present photogrammetry as a reliable step in the fabrication of a full-arch immediate rehabilitation. Materials and Methods: A 59-yearold man attended the department seeking dental rehabilitation for the sequelae of severe oral health neglect. The mandibular teeth suffered from advanced periodontal disease and the patient wore a maxillary complete denture. An irreversible hydrocolloid impression of the mandibular arch was made, poured in stone, and digitally scanned to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…[24][25][26][27][28][29] One study was excluded because it described physical impressions only 30 and another because it was a clinical report. 31 A total of 20 studies published after 2008 were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29] One study was excluded because it described physical impressions only 30 and another because it was a clinical report. 31 A total of 20 studies published after 2008 were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Two main technologies are available for digital scanning: confocal microscopy associated 6 with 3D imaging technologies (Table 2) 19,20,[32][33][34][35][36][37][38][39][40] and photogrammetry. 31,[41][42][43] Photogrammetry relies on photographic images to record the geometrical properties of 3D objects (optical targets) and their interrelated spatial positions. 44 Only 5 clinical studies were retrieved: 1 pilot study, 16 1 prospective study, 45 and 3 randomized controlled trials (RCTs), 40,41,46 with a follow-up of 1 to 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of digital technology, commercially available photogrammetry systems provide a new method for implant impression making for edentulous patients. Some case reports have reported that the photogrammetry system can be successfully used with complete-arch implant impressions with high framework fit [ 32 34 ]. However, current studies on the accuracy assessment of photogrammetry systems are very scarce, and the results are inconsistent [ 17 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the use of photogrammetry was difficult because of the strict need to use special equipment to take images and processing them [ 6 , 27 ]. As some studies reported [ 28 , 29 ], in recent years, due to the advancement of technology in the field of digital photography and the creation of specific software, photogrammetry has become an accurate, reliable, and economically accessible method for most dentists, and it is now becoming an interesting resource in the field. The accuracy of photogrammetry was evaluated in terms of precision (deviation between datasets from the same acquisition method) and trueness (deviation between datasets from different acquisition methods) [ 15 , 26 ].…”
Section: Discussionmentioning
confidence: 99%